The Impacts of Public Transportation Policy on Bus Rapid Transit Operational in the Metropolitan Jakarta - Wahyudi, Ade; Alterkawi, Mezyad M (Universitas Diponegoro, Indonesia, 2023)
The public transportation planning has an essential role in traffic accessibility management. As the urban population grows, the traffic issues also significantly rise and more complex. The problems are traffic casualties, traffic jams, air pollution, and other severe issues. Meanwhile, the DKI Jakarta managed a regulation number 10 in 2014 regarding the bus rapid transit operation in the metropolitan area. Unfortunately, the private vehicle is still favorable since public buses have many drawbacks, particularly in transportation integration and service. The research aims to analyse the impact of public transport policy on Bus Rapid Transit operation in Metropolitan Jakarta. The methodology applies a qualitative approach, where it analyses the current condition of transportation problems. Besides, a deep review of the Master Transportation Plan is conducted to evaluate the potential problems in Bus Rapid Transit Operation. Following that, the impact of transport policy consists of direct impact, indirect impact, and cumulative impact. The PESTEL analysis applies to study the social, economi, environmental, infrastructure, and regulation in BRT management. The result indicated that the social, economic, and environmental aspect has a direct impact on BRT operation. Meanwhile, only the infrastructure aspect is classified as indirect impact since the integration modes only related to the transport demand. Finally, the mitigation strategy is formulated to overcome the BRT problems in Metropolitan Jakarta.